Development of Microcontroller-based Control of a Mini-Flying Robot Application - Hyriel Anuar, Kasdirin; Muhammad Herman , Jamaluddin; Alias , Khamis; Hairol Nizam , Mohd Shah (2010)
This paper elaborate on thedevepment of controller using a PIC-based controller for a flying robot application.